Análisis, interpretación y modelamiento de datos geofísicos de la Cuenca Hornby Bay, Canadá (2020)
Hornby Bay Basin (HBB) is an important uranium and copper mining sector for Canada. This basin is located along the northeast side of Nunavut and is a focus area of studies by Hornby Bay Exploration Ltd. for the purpose of improving understanding of the area and locating mineral resources. For this purpose, in 2004 Hornby Bay Exploration Ltd. contracted the services of Sander Geophysics to obtain and correct high-resolution geophysical data of HBB. In the present document an analysis and modeling of the upper crust structures that conform the Hornby Bay Basin was carried out using gravimetric datasets acquired from public reports of Hornby Bay Exploration Ltd. uploaded to the Nunavut Geoscience online repository. This project was carried out to support the understanding of the main geological structures of the upper crust of the basin. The gravimetric data used in this project was corrected by Sander Geophysics at sea level using an average for the study area of 2.67 g/cm3. With these data it was possible to generate the Bouguer anomaly, which was analyzed and correlated with the regional geology of the basin. In the same way, Bouguer anomaly was used to produce 4 transect modeling on HBB by using the GM-SYS tool of Oasis Montaj of Geosoft. As a result of the project a three-dimensional perspective of the geometry of the structures that make up HBB and its basement, in which the following can be observed: The subsoil of the Hornby Bay Basin is divided by the Wopmay Fault in two geological domains, the eastern basement is divided between the metamorphic Hepburn and Akaitcho lithologies, in contrast, to the west, the basement is formed by the igneous lithologies of Great Bear Magmatic Zone.